Pacemaker-neuron-dependent disturbance of the molecular clockwork by a Drosophila CLOCK mutant homologous to the mouse Clock mutation. - Lee, E.; Cho, E.; Kang, D.H.; Jeong, E.H.; Chen, Z.; Yoo, S.H.; Kim, E.Y. (Proceedings of the National Academy of Sciences of the United States of America, 2016)
Circadian clocks are composed of transcriptional/translational feedback loops (TTFLs) at the cellular level. In Drosophila TTFLs, the transcription factor dCLOCK (dCLK)/CYCLE (CYC) activates clock target gene expression, which is repressed by the physical interaction with PERIOD (PER). Here, we show that amino acids (AA) 657-707 of dCLK, a region that is homologous to the mouse Clock exon 19-encoded region, is crucial for PER binding and E-box-dependent transactivation in S2 cells. Consistently, in transgenic flies expressing dCLK with an AA657-707 deletion in the Clock (Clk(out)) genetic background (pdClk-?;Clk(out)), oscillation of core clock genes' mRNAs displayed diminished amplitude compared with control flies, and the highly abundant dCLK?657-707 showed significantly decreased binding to PER. Behaviorally, the pdClk-?;Clk(out) flies exhibited arrhythmic locomotor behavior in the photic entrainment condition but showed anticipatory activities of temperature transition and improved free-running rhythms in the temperature entrainment condition. Surprisingly, pdClk-?;Clk(out) flies showed pacemaker-neuron-dependent alterations in molecular rhythms; the abundance of dCLK target clock proteins was reduced in ventral lateral neurons (LNvs) but not in dorsal neurons (DNs) in both entrainment conditions. In pdClk-?;Clk(out) flies, however, strong but delayed molecular oscillations in temperature cycle-sensitive pacemaker neurons, such as DN1s and DN2s, were correlated with delayed anticipatory activities of temperature transition. Taken together, our study reveals that the LNv molecular clockwork is more sensitive than the clockwork of DNs to dysregulation of dCLK by AA657-707 deletion. Therefore, we propose that the dCLK/CYC-controlled TTFL operates differently in subsets of pacemaker neurons, which may contribute to their specific functions.